PENGARUH SISTEM PENGAWASAN TERHADAP PRODUKTIVITAS KERJA PEGAWAI DINAS TENAGA KERJA DAN TRANSMIGRASI KABUPATEN KUTAI TIMUR - Yusmilba Yusuf (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
State employee as the government apparatuer in doing the main duty always faced by the complexity of problems. The result shows there is a positive and significant influence from supervision system to the employee’s productivity at Disnakertrans Kutai Timur. Altought actually work productivity also influenced by the other variables, such as leadership, work environment, motivation, education level, amount of employee.